2010
DOI: 10.1111/j.1365-2559.2010.03720.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of BCL2L10 protein expression as prognostic predictor for poor clinical outcome in gastric carcinoma

Abstract: Loss of BCL2L10 protein expression predicts poor clinical outcome in gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Several oncogenes are known to be downregulated in tumors and their low expression predicts a poor prognosis. Clinical studies have shown that low expression of the oncoproteins Bcl-2 and Bcl-B is associated with a poor outcome of GC [32-34]. A similar “discrepancy” has also been noted for some tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 74%
“…Several oncogenes are known to be downregulated in tumors and their low expression predicts a poor prognosis. Clinical studies have shown that low expression of the oncoproteins Bcl-2 and Bcl-B is associated with a poor outcome of GC [32-34]. A similar “discrepancy” has also been noted for some tumor suppressor genes.…”
Section: Discussionmentioning
confidence: 74%
“…Our previous data 2 demonstrated, by immunohistochemistry, that most cancer cells in gastric carcinoma tissue lose the ability to express BCL2L10 protein, in contrast to non‐carcinoma gastric tissues. In the current study, we tested fresh specimens and cancer cell lines for BCL2L10 mRNA and protein content.…”
Section: Resultsmentioning
confidence: 93%
“…We successfully mimicked gastric cancer cells with low levels of BCL2L10 using a murine xenograft model, and found that they showed up‐regulated proliferation in vivo . Interestingly, a retrospective study also revealed a significant correlation between decreased BCL2L10 expression and larger tumour volume in gastric carcinoma 2. The results obtained by cytometry, immunoblotting and PI3K inhibition revealed that growth promotion was associated with PI3K–Akt activated rapid cell cycle progression through the G 1 /S phase, suggesting a potential mechanism of malignancy with low‐level BCL2L10.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, in both study the authors did not study the relation between methylation of the BCL2L10 promoter and modulation of expression of its mRNA or protein level[30]. Of note, in gastric cancer cells methylation of the BCL2L10 promoter seems to correlate with decreased expression of BCL2L10 protein level [31, 32]. Taking into account the discrepancies reported regarding the impact of BCL2L10 promoter methylation status, it appears of great interest to consider its protein rather than its mRNA expression, in agreement with a recent report by Beverly et al [33].…”
Section: Discussionmentioning
confidence: 99%